Evaluation of a biological post-treatment after full-scale ozonation at a municipal wastewater treatment plant. (1st March 2020) - Itzel, Fabian; Baetz, Nicolai; Hohrenk, Lotta L.; Gehrmann, Linda; Antakyali, Demet; Schmidt, Torsten C.; Tuerk, Jochen
Abstract: To reduce the discharge of trace organic compounds into water bodies associated with potential toxic effects such as endocrine disruption, new advanced treatment methods are being investigated at several wastewater treatment plants (WWTPs). One of the most studied and already implemented technologies is ozonation. However, ozonation only partially oxidizes trace organic compounds (TrOC) and as a result, transformation products (TPs) with unknown properties can be formed. In order to minimise the risk of releasing unknown and potentially toxic TPs into surface water, it is recommended to install a biological post-treatment after ozonation. The aim of this study was to evaluate the efficiency of a moving bed reactor following ozonation in a full-scale plant. Different ozone dosages (zspec.  = 0.3, 0.5, 0.7 mg O3 /mgDOC ) were investigated. To assess the biological activity of the post-treatment, the assimilable organic carbon (AOC) was determined in addition to the formed biomass. Furthermore, selected TrOC were analysed in parallel to monitor the ozonation efficiency at different ozone doses. In addition, estrogenic, androgenic as well as corresponding antagonistic effects were investigated after each treatment step using the A-YES and A-YAS assay. A non-target screening was performed to evaluate a trend analysis of formed TPs as well as their removal by the post-treatment procedure. The results proved the successful design of the biological post-treatment reactor by a constant biofilm development and reduction of the AOC. Endocrine effects were removed below the limit of detection (LOD) of 10 pg EEQ/L already after ozonation for all applied ozone doses. Antagonistic effects were not significantly reduced during ozonation and subsequent biological post-treatment. For this reason, further research is needed to evaluate different post-treatment technologies. The trend analysis from non-target screening data showed a reduction of about 95% of the number of formed TPs by the biological post-treatment. Consequently, an assessment of the biological activity and the elimination capacity of a certain biological post-treatment technique is thus possible by applying the AOC in combination with a non-target screening. Graphical abstract: Image 1 Highlights: AOC proved to be a well suited tool for evaluating the post-treatment efficiency. Anti-androgenic effects were neither reduced by ozone nor the post-treatment. Non-target trend analysis showed a reduction of 95% of detected formed TPs.